The relationship of player load and anaerobic performance in different football playing strategies - Mustafa Erol; Ali Enver Kapelman; Ali Kizilet (Physical Education of Students)
Background and Study Aim. The purpose of the present study is to determine the effect of player load on the anaerobic performance of soccer players.